Adoption Intention of Digital Gold Investment: An Integrated Model of UTAUT, Price Value, Perceived Risk, and Attitude as a Mediator in Greater Jakarta, Indonesia - Edwin; Aswin Widyastama Sugianto; Henry Ronald Siahaya; Asnan Furinto (Eduvest - Journal of Universal Studies, 2026)
Gold has traditionally been a store of value and a financial hedge in both developed and emerging markets, including Indonesia. Recent rupiah depreciation and global economic uncertainty have prompted investors to seek safer assets and digital alternatives. This study investigates the factors influencing digital gold investment adoption among Gen X, Millennials, and Gen Z in Greater Jakarta, using an extended UTAUT framework that incorporates price value, perceived risk, and attitude as mediators. A cross-sectional survey and PLS-SEM analysis of 51 respondents assess both direct and indirect effects of UTAUT constructs, economic and psychological factors, and behavioral intention. Results show that performance expectancy, facilitating conditions, and perceived risk significantly affect behavioral intention, while price value strongly influences attitude but not intention directly. The mediating effect of attitude is not supported. These findings suggest that cognitive evaluations, such as utility, readiness, and risk, outweigh affective responses in digital gold adoption among urban Indonesian youth. The study offers theoretical insights for fintech adoption models and practical guidance for digital gold providers, emphasizing platform features, infrastructure, and risk management. Limitations include a small sample size and potential validity concerns, indicating areas for future research.